Child Labour in India Min. of Labour - Ministry of Labour, Labour Bureau, Government of India (Ministry of Labour, Labour Bureau, Government of India, 1954)
The term “child labour” refers both to an economic practice and to the attendant social evil. Child labour as an economic practice signifies employment in gainful occupations and a material contribution to the labour income of the family ; only an age line differentiates it from adult labour. It is more in the concept of a social evil that the term child labour is now used and in assessing the nature and extent of this social evil the character of the jobs on which childrer are engaged, the dangers to which they are subjected and the opportunities of development of which they are deprived should all be taken into account.
Government of India Ministry of Labour, Labour Bureau
Ministry of Labour, Labour Bureau, Government of India